2002
DOI: 10.2337/diacare.25.5.822
|View full text |Cite
|
Sign up to set email alerts
|

Five-Week, Low–Glycemic Index Diet Decreases Total Fat Mass and Improves Plasma Lipid Profile in Moderately Overweight Nondiabetic Men

Abstract: OBJECTIVE -To evaluate whether a 5-week low-glycemic index (LGI) diet versus a highglycemic index (HGI) diet can modify glucose and lipid metabolism as well as total fat mass in nondiabetic men.RESEARCH DESIGN AND METHODS -In this study, 11 healthy men were randomly allocated to 5 weeks of an LGI or HGI diet separated by a 5-week washout interval in a crossover design. RESULTS -TheLGI diet resulted in lower postprandial plasma glucose and insulin profiles and areas under the curve (AUCs) than the HGI diet. A 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
162
3
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(187 citation statements)
references
References 30 publications
16
162
3
5
Order By: Relevance
“…Short-term studies in humans showed lower satiety, increased hunger or higher voluntary food intake in subjects consuming high compared to low GI meals (Ludwig, 2002;Roberts et al, 2002). Weight loss in obese hyperinsulinaemic women was higher in those consuming an energy restricted low compared to high glycaemic diet for 12 weeks (Slabber et al, 1994), and in men lower adiposity was found after consumption of an energy-restricted low glycaemic diet for 5 weeks (Bouche et al, 2002). Although these were all shortterm findings in mostly obese subjects, this mechanism may play a role in normal subjects to maintain normal weight over a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term studies in humans showed lower satiety, increased hunger or higher voluntary food intake in subjects consuming high compared to low GI meals (Ludwig, 2002;Roberts et al, 2002). Weight loss in obese hyperinsulinaemic women was higher in those consuming an energy restricted low compared to high glycaemic diet for 12 weeks (Slabber et al, 1994), and in men lower adiposity was found after consumption of an energy-restricted low glycaemic diet for 5 weeks (Bouche et al, 2002). Although these were all shortterm findings in mostly obese subjects, this mechanism may play a role in normal subjects to maintain normal weight over a longer period.…”
Section: Discussionmentioning
confidence: 99%
“…Several ad libitum trials conducted on nondiabetic subjects have suggested a beneficial effect of low-GI diet on fat mass (Bouche et al, 2002) and body weight (Bouche et al, 2002;Sloth et al, 2004), when compared with high-GI diet, although other trials conducted on subjects with type II diabetes have found no differences in body weight change between high-and low-GI diets (Heilbronn et al, 2002;Jimenez-Cruz et al, 2003;Rizkalla et al, 2004). Additionally, although there has been no association between dietary GI and GL and BMI in some studies (Amano et al, 2004;Liese et al, 2005), other observational studies have shown a positive association between dietary GI, but not dietary GL and BMI Murakami et al, 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, intake of dietary fiber (unavailable carbohydrate) has been shown to be independently negatively associated with a measure of obesity in several (Appleby et al, 1998;Ludwig et al, 1999;Liu et al, 2003;Sasaki et al, 2003;Spencer et al, 2003;Howarth et al, 2005;Liese et al, 2005), but not all (Stookey, 2001), observational studies. Although high dietary fiber intake is often correlated with low dietary GI and/or GL (Howarth et al, 2001;Bouche et al, 2002;Scholl et al, 2004;Schulze et al, 2004;Sloth et al, 2004;Schulz et al, 2005), few observational studies have examined these dietary factors simultaneously in relation to a measure of obesity, especially in non-Western populations (Toeller et al, 2001;Amano et al, 2004;Sahyoun et al, 2005). Clearly, additional studies are needed on the effects of these dietary factors on the development of obesity.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important distinction because a reduction in body fat accompanied by an increment in FFM can result in minor difference in weight yet hold important health benefits (29)(30)(31)(32). Besides, differences in body fat distribution (peripheral and central) may have different impacts on metabolic parameters (11,13,33,34).…”
Section: Obesitymentioning
confidence: 99%